ANALISIS PENGARUH KUALITAS PELAYANAN, FASILITAS DAN HARGA TERHADAP KEPUASAN PELANGGAN (Studi pada Pengguna Jasa Travel IQro’ Semarang) - Puspasari, Maulina; Santosa, Suryono Budi (Faculty of Economics and Business Diponegoro University, 2013)
The purpose of research want to know the effect of quality of service, facilities, and price to customer satisfaction at travel IQro’ Semarang. This study take travel IQro’ as the object because from survey in some travel company in Semarang, travel IQro’ has different marketing strategy than other travel, and also from the data obtained there is a problem is a decrease in passanger quantity.The population in this study are the customers who use the services of travel IQro’ at least twice in the past three months. Sampling in this study using non-probability sampling technique, and the type of purposive sampling method. The analysis used in this study include validity and reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing including t test, F test, and the coefficient of determination (R2).Results of multiple regression analysis is, Y = 0,295 X1+ 0,351 X2+ 0,398 X3. It means that all independent variables, the quality of service, facilities and price have a positive influence on the dependent variable, consumer satisfaction. The independent variable is the most influential is the variable price, followed by a variable facility, and the last is the variable quality of service, and the coefficient of determination (adjusted R2) is 0,773. This means that 77,3% customer satisfaction is affected by prices, facilities and quality of service. While the remaining is influenced by other variables that are not addressed in thisstudy.